Photodynamic therapy for pythiosis - Pires, Layla [UNESP]; Bosco, Sandra de M.G. [UNESP]; da Silva Junior, Nelson F.; Kurachi, Cristina [UNESP] (Wiley, 2013)
Background -  Pythiosis is a life-threatening disease caused by Pythium insidiosum. Photodynamic therapy (PDT) is an alternative treatment to surgery that uses the interaction of a photosensitizer, light and molecular oxygen to cause cell death. Objectives -  To evaluate the effect of PDT on the in vitro growth of P. insidiosum and in an in vivo model of pythiosis. Methods -  For in vitro studies, two photosensitizers were evaluated: a haematoporphyrin derivative (Photogem®) and a chlorine (Photodithazine®). AmphotericinB was also evaluated, and the control group was treated with sterile saline solution. All experiments (PDT, porphyrin, chlorine and light alone, amphotericinB and saline solution) were performed as five replicates. For in vivo studies, six rabbits were inoculated with 20,000 zoospores of P. insidiosum, and an area of 1cm3 was treated using the same sensitizers. The PDT irradiation was performed using a laser emitting at 660nm and a fluence of 200J/cm2. Rabbits were clinically evaluated daily and histopathological analysis was performed 72h after PDT. Results -  For in vitro assays, inhibition rates for PDT ranged from 60 to 100% and showed better results in comparison to amphotericinB. For the in vivo assays, after PDT, histological analysis of lesions showed a lack of infection up to 1cm in depth. Conclusions and clinical importance -  In vitro and in vivo studies showed that PDT was effective in the inactivation of P. insidiosum and may represent a new approach to treating pythiosis. © 2013 The Authors. Veterinary Dermatology © 2013 ESVD and ACVD.
Keywords: chlorine; photosensitizing agent; porphyrin; animal; animal disease; drug effect; infection; microbiology; photochemotherapy; Pythium; rabbit; radiation exposure; skin disease; Animals; Chlorine; Infection; Photochemotherapy; Photosensitizing Agents; Porphyrins; Rabbits; Skin Diseases